THE INCIDENCE AND STRUCTURE OF OPHTHALMOPATHOLOGY OF TUBALARS - A. L. Onischenko; A. V. Kolbasko; M. A. Safronova (Oftalʹmologiâ, 2017)
673 Tubalars have been examined during the expeditions undertaken by the Institute staff. It was 67% of all ethnic groups, compactly living in the Altai Republic. We have also examined 521 Russians and 316 Métis (children of a Russian and an Altaian). The overall incidence of ophthalmopathology (N00-59, Q12-14, D31, S05) at Tubalars amounted to 1965,82 ‰. Among Tubalars the prevalence of eye diseases has been found in females (women — 2075,54 ‰; men — 1896,88 ‰). Age affects the ophthalmopathology incidence in the population of Tubalars. The structure and the incidence of eye diseases in Tubalars has been proven: anomalies of refraction and accommodation disorders (799,40 ‰); conjunctival diseases (390,79 ‰); diseases of the retina (212,48 ‰); disease of the lens (164,93 ‰); other eye diseases and neoplasms of its ancillary apparatus (124,81 ‰); diseases of the lacrimal apparatus (112,93 ‰). Women Tubalars suffered from cataracts more frequently than men (p = 0.045). This is probably due to the higher life expectancy of women and more frequent recording of the age-related cataract in this group. Over the past 25 years the agerelated cataracts in Altaians have been registered in younger age. Age-related cataracts prevailed over other forms of cataract both in Tubalars (148.59 ‰), and Russians (307.1 ‰), Métis (44.3 ‰), and the most common stage of development of senile cataract in Tubalars (90%), Russian (93%) and Métis (93%) was an initial cataract. Retinal Diseases in Tubalars occurred mainly in patients over 30, with the indicators of higher values in the age group 50-59 years (about 456.89%) and 60-69 years (675,78 ‰). In the structure of retinal diseases in all three ethnic groups background retinopathy dominated, among which the first place was occupied by the retinopathy of hypertensive type (p = 0,000). The hypotonic type of retinopathy was less frequent — 16,34 ‰ (for Tubalars p = 0,000). In women, the retinopathy of hypertensive type was recorded 1.5 times higher than in men (p = 0,031).